Effect of pharmacologically induced retinal degeneration on retinal autofluorescence lifetimes in mice. (December 2016) - Dysli, Chantal; Dysli, Muriel; Zinkernagel, Martin S.; Enzmann, Volker
Abstract: Fluorescence lifetime imaging ophthalmoscopy (FLIO) was used to investigate retinal autofluorescence lifetimes in mouse models of pharmacologically induced retinal degeneration over time. Sodium iodate (NaIO3, 35 mg/kg intravenously) was used to induce retinal pigment epithelium (RPE) degeneration with subsequent loss of photoreceptors (PR) whereas N-methyl-N-nitrosourea (MNU, 45 mg/kg intraperitoneally) was employed for degeneration of the photoreceptor cell layer alone. All mice were measured at day 3, 7, 14, and 28 after the respective injection of NaIO3, MNU or NaCl (control). Fluorescence lifetime imaging was performed using a fluorescence lifetime imaging ophthalmoscope (Heidelberg Engineering, Heidelberg, Germany). Fluorescence was excited at 473 nm and fluorescence lifetimes were measured in a short and a long spectral channel (498–560 nm and 560–720 nm). Corresponding optical coherence tomography (OCT) images were consecutively acquired and histology was performed at the end of the experiments. Segmentation of OCT images and histology verified the cell type-specific degeneration process over time. Retinal autofluorescence lifetimes increased from day 3 to day 28 in mice after NaIO3 treatment. Finally, at day 28, fluorescence lifetimes were prolonged by 8% in the short and 61% in the long spectral channel compared to control animals (p = 0.21 and p = 0.004, respectively). In mice after MNU treatment, the mean retinal autofluorescence lifetimes were already decreased at day 3 and retinal lifetimes were finally shortened by 27% in the short and 51% in the long spectral channel at day 28 (p = 0.0028). In conclusion, degeneration of the RPE with subsequent photoreceptor degeneration by NaIO3 lead to longer mean fluorescence lifetimes of the retina compared to control mice, whereas during specific degeneration of the photoreceptor layer induced by MNU shorter lifetimes were measured. Therefore, short retinal fluorescence lifetimes may originate from the RPE and may be modified by the overlaying retinal layers. Highlights: Degeneration of retinal pigment epithelium and photoreceptors by NaIO3 lead to longer retinal autofluorescence lifetimes. Degeneration of the photoreceptor layer by MNU leads to shorter retinal autofluorescence lifetimes. Short retinal fluorescence lifetimes may originate from the RPE and may be modified by the overlaying retinal layers. Fluorescence lifetime imaging ophthalmoscopy can be used to detect pharmacologically induced retinal changes.